1998
DOI: 10.1038/sj.ejcn.1600578
|View full text |Cite
|
Sign up to set email alerts
|

The influence of thermic effect of food on satiety

Abstract: Objectives: To evaluate energy expenditure after three isoenergetic meals of different nutrient composition and to establish the relationship between the thermic effect of food (TEF), subsequent energy intake from a test meal and satiety sensations related to consumption. Design: The study employed a repeated measures design. Ten subjects received, in a randomized order, three meals of 2331 AE 36 kJ (557 AE 9 kcal). About 68% of energy from protein in the high protein meal (HP), 69% from carbohydrate in the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(98 citation statements)
references
References 36 publications
2
94
1
1
Order By: Relevance
“…Dietary composition influences the thermic effect of food (TEF) and it has been observed that a high-protein meal had a greater effect on TEF and was more satiating that either a high-carbohydrate or a high-fat meal (Crovetti et al, 1997). TEF and the sensation of fullness were closely linked in this study.…”
Section: Introductionmentioning
confidence: 52%
“…Dietary composition influences the thermic effect of food (TEF) and it has been observed that a high-protein meal had a greater effect on TEF and was more satiating that either a high-carbohydrate or a high-fat meal (Crovetti et al, 1997). TEF and the sensation of fullness were closely linked in this study.…”
Section: Introductionmentioning
confidence: 52%
“…30,31 The positive association between protein consumption and weight loss might be facilitated by both increased satiety and increased postprandial thermogenesis induced by protein intake. [32][33] In our previous study, body weight loss of obese subjects during a 3-6 months weight management program was related to the increase in reported protein intake. 34 Westerterp-Plantenga et al 35 reported that a 20% increase in protein intake improved weight maintenance after weight loss in moderately obese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies (Crovetti et al, 1998;Mansour et al, 2012;Westerterp-Plantenga et al,1997) suggest that appetite and satiety are influenced by an increase in energy expenditure in the postprandial period due to absorbing, metabolizing, and storing ingested nutrients (Tappy, 1996), a phenomenon known as diet induced thermogenesis. Studies have found that higher diet induced thermogenesis (DIT) is correlated with reduced hunger and more satiety (Crovetti et al, 1998;Mansour et al, 2012;Westerterp-Plantenga et al,1997).…”
Section: Hensd Placebomentioning
confidence: 99%
“…Studies have found that higher diet induced thermogenesis (DIT) is correlated with reduced hunger and more satiety (Crovetti et al, 1998;Mansour et al, 2012;Westerterp-Plantenga et al,1997). Thus, the current study also aimed to find out whether appetite responses following HENSD consumption were related to change in postprandial energy expenditure.…”
Section: Hensd Placebomentioning
confidence: 99%
See 1 more Smart Citation